Industrial training report: Sultan Ismail Petra International Islamic College (KIAS) / Nur Hannani Ahmad Khairudin - Ahmad Khairudin, Nur Hannani (Universiti Teknologi MARA, Perlis, 2023)
Sultan Ismail Petra International Islamic College (KIAS) is my last option for an internship and I was happy to have my internship there. I gained so much experience and improved my skill during this internship. Basically, in this report, it begins with an overview of KIAS's background, mission, and goals, as well as its organizational structure. The training reflections are included in the next section. The training reflections include the training I received while working as an intern at KIAS. This report will go into details on SWOT analysis to examine the organization's strengths, weaknesses, opportunities, and threats. This is followed by recommendation and conclusion and the last part is references and appendices. The purpose of this report is a reflection of a journal that led me to learn and gain knowledge from the company. Lastly, there are appendices that show my contribution during the internship.